miR-222 Suppresses Immature Porcine Sertoli Cell Growth by Targeting the GRB10 Gene Through Inactivating the PI3K/AKT Signaling Pathway - Luo, Hui; Peng, Fuzhi; Weng, Bo; Tang, Xiangwei; Chen, Yao; Yang, Anqi; Chen, Bin; Ran, Maoliang (Frontiers in Genetics, 2020)
Sertoli cells are central and essential coordinators of spermatogenesis. Accumulating evidence has demonstrated that miRNAs participate in the regulation of Sertoli cell growth. However, the functions and regulatory mechanisms of miRNAs in Sertoli cells of domestic animals remain largely unknown. Here, we report that miR-222 overexpression repressed cell cycle progression and proliferation, and promoted apoptosis of immature porcine Sertoli cells, whereas miR-222 inhibition resulted in the opposite result. miR-222 directly targeted the 3′-UTR of the GRB10 gene and inhibited its mRNA abundance. An siRNA-induced GRB10 knockdown showed similar effects as did miR-222 overexpression on cell proliferation and apoptosis, and further attenuated the role of miR-222 inhibition. Furthermore, both miR-222 overexpression and GRB10 inhibition repressed the phosphorylation of PI3K and AKT, the key elements of the PI3K/AKT signaling pathway, whereas GRB10 inhibition offset the effects of the miR-222 knockdown. Overall, we concluded that miR-222 suppresses immature porcine Sertoli cell growth by targeting the GRB10 gene through inactivation of the PI3K/AKT signaling pathway. This study provides novel insights into the epigenetic regulation of porcine spermatogenesis by determining the fate of Sertoli cells.